2020
DOI: 10.1088/1742-6596/1494/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Improved reuse and affinity of enzyme using immobilized amylase on alginate matrix

Abstract: Enzyme immobilizations were widely used to increase their shelf life which is essential for the world’s industries. Therefore, amylase immobilized using Na-alginate as a matrix is necessary optimized and characterized. The parameters measured in the optimization of immobilization are the determination of the concentration of sodium alginate and contact time. Characterizations were conducted to determine the optimum concentration of substrate, the value Vmax, Michaelis-Menten constant (KM), pH, temperature, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…The optimum temperature for α-amylase enzyme catalytic activity of both free and A-BSF enzyme was seen at 50 C (Figure 5). Similarly (Zusfahair et al, 2020), noted that there is no change in the optimum reaction temperature (40 C) before and after immobilization of bacterial amylase. By raising the temperature to 70 C, there is an obvious loss of free enzyme activity by 3.2-fold which is higher than the loss of A-BSF activity (1.4-fold).…”
Section: Characterization Of α-Amylase Enzyme Free and Immobilized On...mentioning
confidence: 97%
“…The optimum temperature for α-amylase enzyme catalytic activity of both free and A-BSF enzyme was seen at 50 C (Figure 5). Similarly (Zusfahair et al, 2020), noted that there is no change in the optimum reaction temperature (40 C) before and after immobilization of bacterial amylase. By raising the temperature to 70 C, there is an obvious loss of free enzyme activity by 3.2-fold which is higher than the loss of A-BSF activity (1.4-fold).…”
Section: Characterization Of α-Amylase Enzyme Free and Immobilized On...mentioning
confidence: 97%
“…It is more difficult to extrude through the syringe needle when the viscosity is high, and, consequently, the formation of microcapsules is not uniform. Zusfahair et al [ 58 ] studied the immobilization of amylase from Aspergillus oryzae and observed a reduction in immobilization yield while increasing alginate concentration. Conformational changes in the entrapped enzyme and limitation of substrate mass transfer to the microcapsules can be caused by increasing sodium alginate concentration.…”
Section: Most Used Polymers For Enzyme Encapsulationmentioning
confidence: 99%
“…polymers) or inorganic support materials are used for entrapment among that sodium alginate is most widely used polymer due to its low cost, easy to use, mild gelling properties, biocompatibility, thermostability, effective particle size, availability and non toxicity (Ding et al,2020). Hence lipase entrapment in calcium alginate beads has shown to be relatively safe and straightforward techniques so in this study lipase was immobilized using calcium alginate beads (Zusfahair et al, 2020). Energy is key factor of economic development of nation.…”
Section: Issn: 2319-7706 Volume 10 Number 04 (2021)mentioning
confidence: 99%
“…There was an increase in immobilization efficiency as the concentration of alginate increases from 1% to 4% (w/v). The lower alginate concentration of 1% resulted in the formation of fragile beads which got disrupted easily and had larger pore sizes resulting in leakage of the enzyme from the beads thereby lowering enzyme activity (Malhotra andBasir, 2020 andZusfahair et al, 2020).The concentration calcium chloride influences the stability and porosity of the beads. Maximum immobilization efficiency and yield (69% & 43%) was recorded from beads prepared from 200mM calcium chloride.…”
Section: Optimization Of Lipase Immobilizationmentioning
confidence: 99%